Facile Guanidine Formation under Mild Acidic Conditions - Takeuchi, Kohei; Nakayama, Atsushi; Tanino, Keiji; Namba, Kosuke (Synlett, 2016)
An efficient method for converting isothioureas into guanidines was developed. The use of amine salts of bis(trifluoromethanesulfonyl)imide as a nitrogen source was found to induce an efficient conversion under weak acidic conditions at 50 °C. The conversion was applicable to the various amines and carbamate-protected thioureas, and various carbamate-protected cyclic guanidines were obtained in high yields. In particular, ammonium bis(trifluoromethanesulfonyl)imide salt is a useful N1 source with which to construct monoprotected cyclic guanidines.
Keywords: guanidinylation; cyclic guanidine; isothiourea; bis(trifluoromethansulfonyl)imide; ammonium bis(trifluoromethansulfonyl)imidate